Phytoconstituents of Androstachys johnsonii Prain Prevent Reactive Oxygen Species Production and Regulate the Expression of Inflammatory Mediators in LPS-Stimulated RAW 264.7 Macrophages - Emmanuel Mfotie Njoya; Gaetan T. Tabakam; Chika I. Chukwuma; Samson S. Mashele; Tshepiso J. Makhafola (Antioxidants, 2024)
According to a survey, the medicinal use of Androstachys johnsonii Prain is kept secret by traditional healers. Considering that inflammation and oxidative stress are major risk factors for the progression of various chronic diseases and disorders, we resolved to investigate the antioxidant and anti-inflammatory potentials of A. johnsonii using in vitro and cell-based assays. The antioxidant activity of A. johnsonii hydroethanolic leaf extract (AJHLE) was evaluated using the ABTS, DPPH, and FRAP assays. Its cytotoxic effect was assessed on RAW 264.7 macrophages using an MTT assay. Then, its anti-inflammatory effect was evaluated by measuring the NO production and 15-LOX inhibitory activities. Moreover, its preventive effect on ROS production and its regulatory effect on the expression of pro-inflammatory mediators such as IL-1β, IL-10, TNF-α, and COX-2 were determined using established methods. AJHLE strongly inhibited radicals such as ABTS•+, DPPH•, and Fe3+-TPTZ with IC50 values of 9.07 µg/mL, 8.53 µg/mL, and 79.09 µg/mL, respectively. Additionally, AJHLE induced a significant (p < 0.05) cytotoxic effect at 100 µg/mL, and when tested at non-cytotoxic concentrations, it inhibited NO and ROS production in LPS-stimulated RAW 264.7 macrophages in a concentration-dependent manner. Furthermore, AJHLE showed that its anti-inflammatory action occurs via the inhibition of 15-LOX activity, the downregulation of COX-2, TNF-α, and IL-1β expression, and the upregulation of IL-10 expression. Finally, chemical investigation showed that AJHLE contains significant amounts of procyanidin, epicatechin, rutin, and syringic acid which support its antioxidant and anti-inflammatory activities. These findings suggest that A. johnsonii is a potential source of therapeutic agents against oxidative stress and inflammatory-related diseases.